Effects of SiO2, CaO and basicity on reduction behaviors and swelling properties of fluxed pellet at different stages - Wang, Ping; Wang, Chaoqiang; Wang, Hongtao; Long, Hongming; Zhou, Tianbao (Powder technology, 2022)
Fluxed pellets are considered as an alternative iron-bearing burden to conserve the energy consumption and to reduce the emissions of blast furnace. In this work, the effects of SiO2, CaO, and binary basicity (w(CaO)/w(SiO2)) on the staged reduction of pellets were experimentally investigated under different conditions, and the related mechanism was elucidated. When the ratio of SiO2 increases from 0% to 7.00%, the reduction degree (RD) of pellets at stage 3 decreases from 93.89% to 75.87%, and the reduction swelling index (RSI) firstly reduces from 26.57% to −12.8% and then increases to −0.3%. Furthermore, with increasing the ratio of CaO, the reduction process of pellets is gradually accelerated, while the swelling performance of pellets shows the distinct differences for different reduction stages. Meanwhile, as the basicity of pellets increases from 0 to 1.33, the RSI of pellets at stage 3 firstly increases from −10.69% to 146.22% and then diminishes to 51.19%. [Display omitted] •The pellets used in this work are prepared with utilizing pure reagents.•The impact mechanisms of SiO2, CaO and basicity on the staged reduction behaviors of pellets were revealed.•The staged reduction swelling properties and mechanism of fluxed pellets were elucidated.